Penerapan Media Pembelajaran Timeline untuk Meningkatkan Minat Belajar dan Keaktifan Siswa di SMAN 3 Ciamis - Rahma, Erischa; Subagja, Royas Aulia; Nurholis, Egi (Jurnal Artefak, 2024)
This study was prepared with the aim of increasing interest and learning activeness in achieving students' understanding of history learning using the application of timeline learning media in class XI F2 students of SMA Negeri 3 Ciamis in the 2024-2025 school year. This type of research is classroom action research with instruments of interview sheets and observation sheets. The subjects of this study were students consisting of 34 students. The object of this research is students' understanding of history learning. The data were analyzed descriptively and presented in the form of tables and graphs. The results showed an increase in activeness and interest in learning in cycle 1 by 26% to 79% in cycle 2, then the understanding of learning the history of students in cycle 1 amounted to 67.6% then in cycle 2 increased to 88.23%. This means an increase of 30.3%. Thus the use of timeline learning media in history subjects can increase interest and activeness in achieving the learning understanding of students in class XI F2 SMA Negeri 3 Ciamis.